C9 immunostaining as a tissue biomarker for periprosthetic joint infection diagnosis - Meinshausen, Ann-Kathrin; Färber, Jacqueline; Illiger, Sebastian; Macor, Paolo; Lohmann, Christoph H.; Bertrand, Jessica (Frontiers in Immunology, 2023)
Background: Culture-negative periprosthetic joint infections (PJI) are often false diagnosed as aseptic implant failure leading to unnecessary revision surgeries due to repeated infections. A marker to increase the security of e PJI diagnosis is therefore of great importance. The aim of this study was to test C9 immunostaining of periprosthetic tissue as a novel tissue-biomarker for a more reliable identification of PJI, as well as potential cross-reactivity. Method: We included 98 patients in this study undergoing septic or aseptic revision surgeries. Standard microbiological diagnosis was performed in all cases for classification of patients. Serum parameters including C-reactive protein (CRP) serum levels and white blood cell (WBC) count were included, and the periprosthetic tissue was immunostained for C9 presence. The amount of C9 tissue staining was evaluated in septic versus aseptic tissue and the amount of C9 staining was correlated with the different pathogens causing the infection. To exclude cross-reactions between C9 immunostaining and other inflammatory joint conditions, we included tissue samples of a separate cohort with rheumatoid arthritis, wear particles and chondrocalcinosis. Results: The microbiological diagnosis detected a PJI in 58 patients; the remaining 40 patients were classified as aseptic. Serum CRP values were significantly increased in the PJI cohort. Serum WBC was not different between septic and aseptic cases. We found a significant increase in C9 immunostaining in the PJI periprosthetic tissue. To test the predictive value of C9 as biomarker for PJI we performed a ROC analyses. According to the Youden’s criteria C9 is a very good biomarker for PJI detection with a sensitivity of 89% and a specificity of 75% and an AUC of 0.84. We did not observe a correlation of C9 staining with the pathogen causing the PJI. However, we observed a cross reactivity with the inflammatory joint disease like rheumatoid arthritis and different metal wear types. Also we did not observe a cross reactivity with chondrocalcinosis. Conclusion: Our study identifies C9 as a potential tissue-biomarker for the identification of PJI using immunohistological staining of tissue biopsies. The use of C9 staining could help to reduce the number of false negative diagnoses of PJI.